Associations between in utero exposure to polybrominated diphenyl ethers, pathophysiological state of fetal growth and placental DNA methylation changes. (December 2019) - Zhao, Yingya; Song, Qi; Ge, Wenzhen; Jin, Yuting; Chen, Shangqin; Zhao, Yan; Xiao, Xirong; Zhang, Yunhui
Highlights: In utero PBDEs exposure was associated with fetal growth retardation. Fetal growth was associated with aberrant methylation of HSD11B2 or IGF2. Both HSD11B2 and IGF2 methylation were related to exposure to lower BDE congeners. IGF2 methylation partially mediated the effects of BDE-17–190 on fetal growth. PBDEs exposure might disrupt fetal growth by affecting placental DNA methylation. Abstract: Background: Polybrominated diphenyl ethers (PBDEs) are environmental chemicals with harmful effects on pregnancy, but their effects on adverse developmental outcomes are not fully understood. The placental DNA methylation is strongly influenced by prenatal environmental factors and has been linked to fetal growth. Objective: To evaluate the association between in utero PBDEs exposure, placental DNA methylation changes (growth regulatory genes), and pathophysiology of fetal growth (birth outcomes, fetal growth retardation) in a population-based pregnancy cohort study. Methods: This was a nested case-control study within the prospective Wenzhou Birth Cohort including 130 fetal growth retardation (FGR) cases and 130 healthy controls and their mothers recruited from June 2016 to June 2017. FGR was diagnosed based on the comprehensive evaluation of ultrasound results at 24, 28, and 32 weeks of gestation. Neonatal birth measurements were obtained from medical records. Gestational exposure to 19 PBDEs, including 13 lower BDE congeners (BDE-17–190) and 6 higher brominated BDE congeners (BDE-196–209), were determined by gas chromatography tandem mass spectrometry in the umbilical cord blood. Placental DNA methylation changes of one repetitive element ( LINE1 ) and two candidate genes ( HSD11B2, IGF2 ) were characterized by quantitative polymerase chain reaction-pyrosequencing. Multiple linear regression and logistic regression models were used to examine the associations among PBDEs exposure, fetal growth indicators, and DMR (differential methylation region) methylation fractions. Sobel tests were conducted to assess DNA methylation as a mediator in multivariate models. Results: After excluding women who withdrew from the study or were lost to follow-up or failed to provide placenta or umbilical cord blood, 249 mother-newborn pairs (124 FGR cases, 125 controls) were included in the final analysis. Elevated BDE-206 (OR: 1.569, 95% CIs: 1.053–2.338), BDE-17–190 (OR: 2.860, 95% CIs: 1.233–6.634), BDE-196–209 (OR: 1.688, 95% CIs: 1.024–2.783) and ∑19 PBDEs (OR: 2.387, 95% CIs: 1.220–4.668) concentrations were associated with increased risk of FGR in newborns. FGR birth was also associated with increased DNA methylation of HSD11B2 (OR: 1.145, 95% CIs: 1.032–1.270) and decreased DNA methylation of IGF2 (OR: 0.892, 95% CIs: 0.845–0.941). In addition, BDE-17–190 showed significant associations with DNA methylation of HSD11B2 and IGF2 (β: 1.127, 95% CIs: 0.069–2.186; β: −3.452, 95% CIs: −5.512–1.392), indicating placental DNA methylation changes of HSD11B2 and IGF2 were related to both lower BDE congeners exposure and fetal growth. Further mediation analyses showed that IGF2 methylation mediated about 40% of the effects of BDE-17–190 in umbilical cord blood on neonatal FGR. Conclusion: We report an inverse association between in utero exposures to PBDEs and fetal growth and provide evidence supporting epigenetic gene plasticity in these associations. Changes in placental DNA methylation might be part of the underlying biological pathway between prenatal PBDEs exposure and adverse fetal growth.